Recommendation Algorithm of Web-Based Learning Resources considering Timeliness and Popularity. (7th October 2022) - Han, Xiaolu
Abstract : The optimized learner evaluation matrix and similarity model are essential methods to deal with the challenges of "data sparsity" and "cold start" in the process of learning resource recommendation on the online learning platform. Accordingly, an improved collaborative filtering algorithm (TRCP) is proposed to improve the accuracy of learning resource recommendation. The TRCP algorithm generates the learner evaluation matrix for recommended projects by classifying learning resources. It comprehensively considers the influence of learners' online learning behavior, learning time, and popularity of learning resources on learners' interest and optimizes the sample data in the evaluation matrix. The experimental results on the school online teaching platform verified that this method has achieved obvious and effective results in both the accuracy and satisfaction rate of learning resource recommendation.